Heuristic approach to modelling continuing education on the example of green chemistry disciplines - Karol, Andrey D.; Zuraev, Alexander V.; Savitskaya, Tatsiana A.; Kimlenka, Iryna M. (University Pedagogical Journal, 2025)
The paper shows the implementation of the heuristic educational situation cycle and the introduction of a successful model of lifelong learning in the school – university system in the process of teaching the academic discipline «Green сhemistry» at the Belarusian State University. The examples of open (heuristic) tasks and educational products created as a result of their fulfilment are demonstrated.
Keywords: heuristic learning; open task; continuous education; green chemistry